A review on energy generation from manure biomass. (2021) - Sasikumar, C.; Sundaresan, R.; Nagaraja, M.; Rajaganapathy, C.
Abstract: Solid biomass with high carbon content such as dried manure can be burnt after moisture removal to heat water for any processing and to drive gas turbines to generate electricity. Biomass energy has potential to contribute 45%–55% of total global energy requirements. Biomass energy contributes a major source of renewable energy since it will not pollute the environment by emission of toxic gases and traces of other metal elements. This paper focuses on utilization of manure biomass as a base fuel for power generation in villages where surplus animal wastes can be extracted and processed. The technical aspects of gasification using animal manures as a source of biomass fuel is described with an awareness to gas cleaning requirements to maintain environmental standards. The main idea of present research is to demonstrate the feasibility of generation electricity from animal residues using the concepts of gasification process. Also the present works addresses the possible technical breakthroughs.